POVERTY X SOCIAL INCLUSION: POLITICAL, SOCIAL AND ENVIRONMENTAL DILEMMAS AND CHALLENGES (ESMAT Magazine, 2018)
This article deals with the conditions of impoverishment and social exclusion, in which there are vast social segments in all the quadrants of the planet, the main objective is to identify the current political, social and environmental dilemmas and challenges and to discuss the strategies and mechanisms adopted to promote of social inclusion, via citizenship and sustainable development. Poverty and social exclusion are treated in a structural and integrated way, in a critique of the logic of care and focused on a logic of social integration and universalization of rights and opportunities, in a critique of interventions that aim only to reduce or minimize the social effects of poverty.